Melanonychia striata: a case report - Nurasta, I. Gede Narendra Yogi Swara; Adiputra, Putu Anda Tusta; Dwipayana, A.A. Krisna (International Journal of Research in Medical Sciences, 2021)
Melanonychia striata longitudinalis is a pigmented band in the long axis of the nail. The discoloration occured because of increase of melanin in the nail matrix. In most cases, especially in children, melanonychia striata is a benign condition. In this case report a 12-years-old male with melanonychia striata. Longitudinal excision was performed with histopathology examination to rule out malignancy and further management.